The tourist route system – models of travelling patterns - Thor Flognfeldt jr. (Belgeo)
Examining tourism is mostly taking place on a site or regional level. Travel, however, is a movement between such sites – from home to destination(s) and back to home again (Leiper, 1979). Trying to view tourism as a movement and a dynamic function means challenges. This paper is an attempt of modelling a “tourist route system” and to show what the use of different travelling pattern models means to “tourism route research” The aim is to show what dimensions will be lacking if studies only are focused on markets, sites or destinations.